BUDAYA HUKUM DALAM MENINGKATKAN KESADARAN APARATUR PEMERINTAH DI KOTA BANJAR PROVINSI JAWA BARAT - Baiq Aprimawati (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2019)
The research was conducted in Banjar City, of Wes Java Province. The title of this research is Culture of Law in Layer Terrace Conescious a Ware Apparatus Government in Banjar City of Wes Java Province. There fore, the author study on the Culture of Law in Layer Terrace Conescious a Ware Apparatus Government in Banjar City of Wes Java Province tions currently based assessment parameters include clarity of purpose, appropriate institutions, conformity and hierarchy as well as the type of content material, can or not, clarity of formulation, and openness. The author also studies about barriers experienced by the Culture of Law in Layer Terrace Conescious a Ware Apparatus Government in Banjar City of Wes Java Province, so the author can write strategy in forming a quality Culture of Law in Layer Terrace Conescious a Ware Apparatus Government in Banjar City of Wes Java Province. This thesis studies conducted in Culture of Law in Layer Terrace Conescious a Ware Apparatus Government in Banjar City of Wes Java Province. Keywords : Culture of Law, Layer Terrace Conescious , Apparatur Government